A Historic Development of the Town Hall Lahore, Pakistan: Viability Analysis for Refurbishment to Attain its Cultural Identity - Jabeen, Asia; Javaid, Rida; Bilal, Areesha (Pakistan Languages and Humanities Review, 2023)
This research paper is an attempt to explore the practical viability of conservation and rehabilitation of historic buildings in terms of their socio-cultural and historic merits. Recent developments and refurbishments have influenced the historic environment of the heritage sites at the cost of their historic integrity and identity. Victoria Jubilee Town Hall, Mall Road Lahore was constructed to function as a seat of the Civic Government during British period on the occasion of Golden Jubilee of the Queen Victoria. The historic monument is located at the finale of Mall Road Lahore and reflects a beautiful combination of Mughal, sultanate and Spanish architectural elements. The historic monument is deteriorating and it needs the attention to be conserved and restored, being a legacy of British period. The glory of the Mall Road Lahore can never meet its climax without mentioning the grandeur of Town Hall. In the conclusion, historic monuments and heritage sites which are learning institutions in themselves should be preserved and regenerated with focused plans.